Stasis, Charging the Space of Change - Sarah Riviere (Footprint)
This article fossicks through the fragments of historical understandings of the word stasis in ancient Greece – where stasis, in its extreme state, involved conflictual hostilities between kindred parties, often termed ‘civil war’ today. Through a series of readings of ancient Greek texts on topics ranging from pathology to literature and politics, stasis is revealed as a powerfully charged state of located dynamic exchange that operates through a precise temporal and spatial performance. This article teases out relevant aspects of the state of stasis – its high levels of spatial engagement, its inevitable resolution into energetic productivity, its precise restraint, its demand for full participation, and its role in the integration of change – all of which were acknowledged as part of the enactment and resolution of a stasis at that time. The intention of this article is to resurrect a more nuanced understanding of the state of stasis that can enrich current concepts of the dynamic in architectural and urban discourse. This understanding of stasis also poses new questions for the future design of spaces that can accommodate charged kindred engagement: lively spaces where contest becomes opportunity, and located spaces of kindred understanding that promise productive reconciliation as the common aim of all the parties involved.